A comparative study of internal organs of silkworm species (Bombyx mori, Samia ricini, Antheraea mylitta, Antheraea assamensis) using stereo-zoom microscopy - Harshitha Prakash; Pawan Shukla; Gangavarapu Subrahmanyam; Himanshu Dubey; Rajal Debnath; K. P. Arunkumar; B. S. Harshitha; Ranjana Gautam; S. Manthira Moorthy (Zoomorphology, 2026)

Study on the Mechanical, Microstructural, and Environmental Assessment of Concrete Containing High Volume Fly Ash and Waste Tyre Steel Fibers - Sankar B; Rameshkumar D; Gautham Kishore Reddy; Arunkumar K; Vishnuprasad V Prabhakar; Anamika S M (Circular Economy and Sustainability, 2026)

A reliable design on real-time electrochemical detection of 5-nitro-2-furaldehyde in various foods and biofluids using NiCo2O4@ g-C3N4 matrix - B. Sudharsan Bangaru; Arunkumar Selvam; Asma A. Alothman; S.K. Suresh Babu; Chih-Yu Kuo; Mani Govindasamy (Chemical Engineering Journal, 2026)

Concept of Integrating Air Conditioning System with Thermoelectric Units and Double-Pipe Heat Exchanger for Efficient Waste Heat Utilization: An Experimental study - B. Manoj; U.C. Arunachala; H.S. Arunkumar (International Journal of Refrigeration, 2026)

Eco-friendly synthesis of CuO nanoparticles using charcoal extract:Sustainable approach and mechanistic study of RhB dye degradation - M. Jothibas; B. Arunkumar; Abishake David Padmarajan; Kartheka Anandan; R. Sweet Stanly; Agalya Mathivanan; R. Piriyadharsini (Nanotechnology for Environmental Engineering, 2026)

Hybrid PCM-embedded concrete for thermal energy storage and energy-efficient smart buildings - S. Deepa Shri; Ali B. M. Ali; Arunkumar Munimathan; Ratchagaraja Dhairiyasamy; M. Kannan; Mukhtar Hamid Abed; Mohammad Amir Khan; Aseel Smerat (Innovative Infrastructure Solutions, 2026)

Fruitful design of novel synthesis of aluminium boride–f-CB nanocomposite for real-time electrochemical sensing of mercury ions in environmental water samples - Arunkumar Selvam; B. Sudharsan Bangaru; Kuei-Chih Feng; S.K. Suresh Babu; Zahra Bayhan; Awatif Alshamari; Chih-Yu Kuo; Mani Govindasamy (Journal of Water Process Engineering, 2025)

Green synthesis of silver nanoparticles using Ocimum sanctum for efficient Congo red dye removal: a response surface methodology approach - S. Murugeshwari; B. Senthil Rathi; N. Kalaiarasi; R. M. Saravana Kumar; I. Arunkumar; M. Vasanth; P. Senthil Kumar; Gayathri Rangasamy (Environmental Monitoring and Assessment, 2025)

Cleaner production of performance-enhanced hybrid composites using agro-industrial wastes: A sustainable waste management strategy - B. Prabhu; M. Prakash; N. Ramasamy; Viswanathan Kanagasabai; T. Mohanraj; D. Vijay; T. Arunkumar (Journal of Environmental Management, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Prospectus of hydrogen enrichment in internal combustion engines: Methodological insights on its production, injection, properties, performance and emissions - J. Jayaprabakar; T. Arunkumar; Gayathri Rangasamy; J. Parthipan; M. Anish; Gaddey Varshini; B. Kiran Kumar (Fuel, 2024)

Nutritional, anti-nutritional and morphological characterization of wild edible species of Solanum found in North East India - Rina Ningthoujam; Chandra Deo; Arunkumar Phurailatpam; B. N. Hazarika; Nangsol Dolma Bhutia; Punabati Heisnam; Mayanglambam Chandrakumar; Yengkhom Disco Singh (Genetic Resources and Crop Evolution, 2024)

Mitigating abiotic stresses using natural and modified stilbites synergizing with changes in oxidative stress markers in aquaculture - D. Arunkumar; K. K. Krishnani; Neeraj Kumar; B. Sarkar; A. K. Upadhyay; P. B. Sawant; N. K. Chadha; R. Abisha (Environmental Geochemistry and Health, 2023)

The impacts of Mn ion incorporation on the structural, optical, and magnetic properties of hematite NPs - S. James Jayaseelan; K. Parasuraman; D. Benny Anburaj; M. Jothibas; B. Arunkumar (Nanotechnology for Environmental Engineering, 2023)

Morphological and biochemical resistance traits of tomato cultivars against thrips and bud necrosis virus disease - B Jamuna; M Bheemanna; Hn Timmanna; Arunkumar Hosmani; Kandapal Kavita (International Journal of Tropical Insect Science, 2021)

Release modulation of highly water soluble drug using solid dispersion: impact of dispersion and its compressed unit - Punit B. Parejiya; Bhavesh S. Barot; Hetal K. Patel; Dharmik M. Mehta; Pragna K. Shelat; Arunkumar Shukla (Journal of Pharmaceutical Investigation, 2014)

Molecular characterization of intercellular adhesion gene in Staphylococcus aureus isolated from bovine mastitic milk - Somanath Kundalik Chavhan; Dewanand Rajaram Kalorey; Anshuja Arunkumar Nagdive; Hemant J. Purohit; Sukhadeo B. Barbuddhe; Nitin Vasantrao Kurkure (Tropical Animal Health and Production, 2012)